Knitted lace of Estonia techniques, patterns, and traditions - Bush, Nancy,$d1951- (Loveland, Colo Interweave Press, 2008)
"Deepen your knowledge of knitting in Estonia with this in-depth look at the west coast town of Haapsalu, its knitting traditions, and how to make them your own. Estonian knitting authority Nancy Bush has researched traditional lace-making techniques and in 'Knitted Lace of Estonia' offers modern adaptations of the classic ways to construct shawls and scarves" --Cover, p. 4
The lace knitting of Haapsalu -- How to knit a Haapsalu sall -- The projects: Queen silvia shawl -- Triangular scarf in leaf pattern -- Peacock tail and leaf scarf -- Lehe square shawl -- Raha scarf -- Leaf and nupp shawl -- Maikell shawl -- Madli's shawl -- Triangular summer shawl -- Lily of the valley scarf -- Lilac leaf shawl -- Miralada's triangular shawl -- Triinu scarf -- Crown prince square shawl -- Estonian lace stitch dictionary -- Abbreviations -- Sources for yarns -- Bibliography
Includes bibliographical references (p. 158) and index
1
Keywords: Knitted lace 650 -- Estonia -- Patterns; knitted lace -- Estonia -- Haapsalu